Pengaruh Jenis Kelamin dalam Variasi Indeks Prestasi Kumulatif Mahasiswa Kedokteran di Universitas Pembangunan Nasional Veteran Jakarta - Makkiyah, Feda Anisah; Harfiani, Erna; Anisah, Anisah (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2019)
The number of female medical students outweigh the number of male students in Indonesia and also in school of medicine universitas Pembangunan Nasional Veteran Jakarta has raised the awareness of identification of role of gender in student learning and student assessment. This study explored the differences of Grade Point of Average in six semesters of medical students based on gender and showed the difficult topics in learning medicine. This study was also as a preliminary study of long term evaluation of medical education process. Methods: This descriptive cohort study explored the GPA scores of medical students of year 2015 that have undergone 6 semesters. The data was analyzed for normal distribution and non parametric study was used as final step to analyze the correlation between gender and performance of medical students in 6 semesters. Result. The highest GPA score was in first semester and the lowest GPA score is in the sixth semester. After first semester, the score steps down in second semester and climbed up again in semester 3 and 4 . The score then decrease to the lowest point in semester 5 and 6. This study also showed there was no significant gender difference of variation of GPA in six semester (P 0,113) and female students have higher GPA scores than male students in all six semester. Conclusion. There was no gender difference in Grade of Point Average score in six semester of medical students in Universitas Pembangunan Nasional VeteranJakarta and semester 5 and 6 were semester that students have low GPA.